The use of propensity score matching to assess the effectiveness of the endometrial receptivity analysis in patients with recurrent implantation failure - Shuang Yu; Yongjie Zhang; Na Li; Zhuolun Su; Wenjing Li; Hua Lou; Yichun Guan (Frontiers in Endocrinology)
BackgroundOne potential cause of implantation failure is abnormal endometrial receptivity, and how to objectively evaluate endometrial receptivity has been a matter of great concern. Endometrial receptivity analysis (ERA), a next-generation sequencing-based test that assesses endometrial gene expression, may be valuable in predicting endometrial receptivity, but whether ERA improves pregnancy outcomes in patients with recurrent implantation failure (RIF) is currently controversial. The purpose of this study was to investigate the effect of ERA on pregnancy outcomes in patients with RIF.MethodsWe performed a retrospective cohort study analysis for a population of patients with RIF undergoing frozen embryo transfer (FET) cycles in the reproductive center of the Third Affiliated Hospital of Zhengzhou University from January 2019 to December 2022(n=1598). FET cycles with personalized embryo transfer (PET) under ERA guidance were included in the ERA group (n=43); after using propensity score matching (PSM), a total of 120 FET cycles were included as a control group. Pregnancy outcomes were compared between the two groups. Further, the relationship between the number of previous implant failures and the rate of implant window displacement was discussed. The factors affecting the window of implantation (WOI) displacement were also assessed.ResultsThere was no statistically significant difference in embryo implantation rate, clinical pregnancy rate, spontaneous abortion rate, and live birth rate between the ERA group and the matched control patients (P > 0.05). There was no significant difference in the rate of WOI displacement between patients in the moderate or severe groups (P > 0.05) and no significant difference in pregnancy outcome ( P>0.05). Finally, analysis of the clinical data of patients in the receptive and non-receptive groups did not uncover any factors influencing WOI displacement.ConclusionThe results of the study showed no significant difference in pregnancy outcomes in patients who received ERA compared to those who did not.